Genome-wide association analysis for drought tolerance and associated traits in faba bean (Vicia faba L.) - Gutiérrez, Natalia; Pégard, Marie; Balko, Christiane; Torres, Ana M. (Frontiers in Plant Science, 2023)
Faba bean (Vicia faba L.) is an important high protein legume adapted to diverse climatic conditions with multiple benefits for the overall sustainability of the cropping systems. Plant-based protein demand is being expanded and faba bean is a good candidate to cover this need. However, the crop is very sensitive to abiotic stresses, especially drought, which severely affects faba bean yield and development worldwide. Therefore, identifying genes associated with drought stress tolerance is a major challenge in faba bean breeding. Although the faba bean response to drought stress has been widely studied, the molecular approaches to improve drought tolerance in this crop are still limited. Here we built on recent genomic advances such as the development of the first high-density SNP genotyping array, to conduct a genome-wide association study (GWAS) using thousands of genetic polymorphisms throughout the entire faba bean genome. A worldwide collection of 100 faba bean accessions was grown under control and drought conditions and 10 morphological, phenological and physiological traits were evaluated to identify single nucleotide polymorphism (SNP) markers associated with drought tolerance. We identified 24 SNP markers significantly correlated with these traits under drought stress conditions. The flanking sequences were blasted to the Medicago truncatula reference genome in order to annotate potential candidate genes underlying the causal variants. Five of the SNPs, accounting for the highest percentages of maturity date, seeds per plant, plot yield and free proline content, correspond to uncharacterized proteins indicating the presence of novel genes associated with drought tolerance in faba bean. The significance of stress-inducible signal transducers provides valuable information on the possible mechanisms underlying the faba bean response to drought stress, thus providing a foundation for future marker-assisted breeding in the crop.